Moving the Wheels of the Village Economy: Empowering Madasar BUMDES Towards Independence and Sustainability - Ni Made Intan PRILIANDANI; I Gusti Ayu Athina WULANDARI; Anak Agung Gde Krisna PARAMITA (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
The purpose of implementing this community service program is to strengthen the capacity of BUMDes Madasar in Dauh Peken Village, Tabanan Regency, through three main areas of intervention: financial literacy, business cooperation strategies, and digital marketing. Assistance was provided to support the preparation of financial reports in accordance with SAK EMKM standards, which are essential for accountability and transparency in business management. BUMDes Madasar, as a newly developing institution with small-scale business units, has limited managerial capacity and technical expertise, especially in financial reporting. Through participatory training, administrators learned to prepare cash flow statements, profit and loss reports, and simple balance sheets. Evaluation results showed that 87.5% of participants could independently prepare financial reports, indicating significant knowledge improvement. In terms of business strategy, mentoring focused on enhancing cooperation with third parties to expand business units and increase village income. Training included partnership simulations, proposal development, and drafting agreements, with 62.5% of participants successfully initiating collaboration with private partners. This capacity strengthens BUMDes’ bargaining position and creates broader opportunities for business growth. Furthermore, digital marketing assistance introduced administrators to social media platforms, online marketplaces, and content creation tools. Post-training evaluations showed that 87.5% of participants expressed a strong need for social media marketing strategies, highlighting the relevance of this intervention. By utilizing digital platforms, BUMDes Madasar is now better equipped to increase its competitiveness and product visibility.